Prognostic value of quantitative high-speed myocardial perfusion imaging - Nakazato, Ryo (2012)
BACKGROUND: Most studies have reported using semi-quantitative analysis to assess the prognostic utility of SPECT myocardial perfusion imaging (MPI). Thus we studied the prognostic value of fully automated quantitative analysis software applied to new solid-state, high-speed (HS) SPECT-MPI. METHODS: 1613 consecutive patients undergoing exercise or adenosine HS-MPI were followed for 2.6±0.5 years for all-cause mortality (ACM). Automated quantitative software was used for assessing stress total perfusion deficit (sTPD) and was compared to semi-quantitative visual analysis. MPI was characterized as 0% (normal); 1–4% (minimal perfusion defect); 5–10% (mildly abnormal); and >10% (moderately/severely abnormal). RESULTS: During follow-up, 79 patients died (4.9%). Annualized ACM increased with progressively increasing sTPD; 0% (0.87%), 1–4% (1.94%), 5–10% (3.10%) and >10% (5.33%) (log-rank p<0.0001). While similar overall findings were observed with visual analysis, only sTPD demonstrated increased risk in patients with minimal perfusion defects. In multivariable analysis, sTPD >10% was a mortality predictor (HR 3.03, 95% CI 1.30–7.09, p=0.01). Adjusted mortality rate was substantial in adenosine MPI, but low in exercise MPI (9.0% versus 1.0%, p<0.0001). CONCLUSIONS: By quantitative analysis, ACM increases with increasing perfusion abnormality among patients undergoing stress HS-MPI. These findings confirm previous results obtained with visual analysis using conventional Anger camera imaging systems.